Investment-Risk Protection Rider for Unit-Linked Insurance - Gunawan, Kenneth; Margaretha, Helena; Winayaka, Yoseph Wastu (Persatuan Aktuaris Indonesia, 2025)
This paper designs an investment-risk protection rider that provides annual return bounds (a floor and a cap) at no explicit cost to the policyholder. The study models two scenarios using the Indonesia Stock Exchange Composite Index (IHSG) as the underlying asset: the first assumes the availability of derivative options to form a zero-cost collar, while the second assumes no options are available, forcing the company to use delta-neutral dynamic hedging. A primary novelty of this research is the demonstration of theoretical option pricing on non-normal return assets and the formulation of a